Incidence, Natural History and Risk Factors of Deep Vein Thrombosis in Elective Knee Arthroscopy - Delis, K. T.; Hunt, N.; Strachan, R. K.; Nicolaides, A. N. (Thrombosis and Haemostasis, 2001)
Aims: to determine the incidence, anatomical distribution and extent of deep vein thrombosis (DVT) in limbs undergoing elective unilateral knee arthroscopy without active prophylaxis, to evaluate its effect on venous function following early diagnosis, and to quantify the impact of risk factors on its incidence. Methods: 102 consecutive patients undergoing unilateral knee arthroscopy without prophylaxis were studied. A history was obtained with emphasis on the risk factors for thromboembolism, and physical examination and colour duplex were performed prior to and within a week after surgery. Patients who developed calf DVT were given aspirin (150 mg) and compression stockings; those with proximal DVT were admitted for anticoagulation (heparin followed by warfarin). Follow-up (mean 118 [range 84-168] days) entailed weekly physical and duplex examinations during the first month and monthly thereafter. Results: 8 patients developed calf DVT in the operated leg (incidence 7.84% [95% Cl: 2.7%-13.2%]); thrombosis was asymptomatic in 4 of those (50%), caused calf tenderness in 4 (50%) and a positive Homan’s sign in one (12.5%). DVT occurred in the following veins: peroneal 4 subjects (50%), soleal 4 (50%), gastrocnemial 2 (25%) and tibial 2 (25%). Propagation of a calf DVT to the popliteal vein was identified in 1 patient (12.5%). After a median period of 118 days, total clot lysis was found in 50% of DVTs, with partial thrombus resorption in the rest; reflux in the thrombosed veins was present in 75% of limbs with DVT. 43% of patients had 1 risk factor for DVT and 20% had ≥2. The incidence of DVT was higher amongst those with two or more risk factors for thromboembolism (p <.05) or those with previous thrombosis alone (p <.005). Symptoms or signs of pulmonary embolism were not documented. Conclusions: Elective unilateral knee arthroscopy performed without prophylaxis is complicated by ipsilateral calf DVT in 7.8% (95% CI: 2.7%-13.2%) of cases. The risk is higher in the presence of previous thrombosis (relative risk: 8.2) and two or more risk factors for DVT (relative risk: 2.94). Thrombosis may propagate to the proximal veins, despite early diagnosis. 50% of calf clots totally lyse in 4 months, yet reflux develops in at least 75% of limbs with DVT. Further studies to determine optimal prophylaxis are warranted.
Keywords: Thrombosis; knee; arthroscopy